Balkanische Spezifika des Nexus Sprache – Ethnizität als Methodenreflexion - Voß, Christian (Zeitschrift für Balkanologie, 2008)
The multioptional, fluid identity patterns of South European linguistic minorities are an ideal example for the negotiation of collective identities beyond the ethnonational logic equating language, nation and territory as developed by German political romanticism. Border minorities in the Balkans linguistically symbolise their hybrid bilingual identity, which rejects any form of one-dimensional national association. Language ideology of such groups has to be seen as an Ottoman legacy: The conflation of Greekness and Christianity as well as of Turkishness and Islam is in a position to deessentialise the link between language, culture and ethnic identity. Using Howard Giles’ ‘ethnic boundary model’ we can prove that language nationalism at the grass-root level is still not at home in the Balkans. In the first part, the paper traces the methodological development of research dealing with code-switching (from grammatical via pragmatic to anthropological and cognitive approaches) illustrated by Bulgarian-Greek, Macedonian-Greek, Slovenian-Serbian and Bulgarian-Romanian examples. In the second part, multilingualism in the Balkans is discussed in the context of the recent discussion started by Uwe Hinrichs comparing the so-called Balkansprachbund with creole languages. The morphosyntactic structure of the Balkan languages combining extreme archaism with radical analytic forms due to linguistic convergence has to be explained as partial accommodation as described by Howard Giles since the 1970s: In the context of constant migration movements language communities in the Balkans accommodated to their linguistic neighbours, but simultaneously diverged as a tactic of intergroup distinctiveness.